Visual categorization and the parietal cortex - Fitzgerald, Jamie K.; Swaminathan, Sruthi K.; Freedman, David J. (Frontiers in Integrative Neuroscience, 2012)
The primate brain is adept at rapidly grouping items and events into functional classes, or categories, in order to recognize the significance of stimuli and guide behavior. Higher cognitive functions have traditionally been considered the domain of frontal areas. However, increasing evidence suggests that parietal cortex is also involved in categorical and associative processes. Previous work showed that the parietal cortex is highly involved in spatial processing, attention and saccadic eye movement planning, and more recent studies have found decision-making signals in LIP. We recently found that a subdivision of parietal cortex, the lateral intraparietal area (LIP), reflects learned categories for multiple types of visual stimuli. Additionally, a comparison of categorization signals in parietal and frontal areas found stronger and earlier categorization signals in parietal cortex, arguing that parietal abstract association or category signals are unlikely to arise via feedback from prefrontal cortex (PFC).